2017
DOI: 10.1155/2017/1765460
|View full text |Cite
|
Sign up to set email alerts
|

Primary Villoglandular Mucinous Adenocarcinoma of the Vulva

Abstract: Primary villoglandular mucinous adenocarcinoma of the vulva is rare tumor. We report a case of 68-year-old woman who developed this very uncommon malignant tumor. Immunohistochemical examination of this tumor revealed positive staining for Cytokeratin 20, Mucin 2, and CDX2, although Cytokeratin 7 and Mucin 6 were negative. This positive staining indicated the tumor enteric type characters. In order to exclude the possibility of the metastasis from another site, we thoroughly evaluated clinical data and extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Immunohistochemistry plays a determinant role in the diagnosis. Unlike most Müllerian tumors of female genital tract, adenocarcinoma of intestinal type very often overexpresses CK20 and less often CK7 (23). However, a few cases have also reported expression simultaneously of CK 7 and CK20 (8).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry plays a determinant role in the diagnosis. Unlike most Müllerian tumors of female genital tract, adenocarcinoma of intestinal type very often overexpresses CK20 and less often CK7 (23). However, a few cases have also reported expression simultaneously of CK 7 and CK20 (8).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, in this case, the results of high-risk-HPV testing were not provided [ 29 ]. Other authors reported the association with high-risk HPV (HPV 16, detected by in situ hybridization) in one case of vestibular adenocarcinoma in situ [ 20 , 36 ]. However, none of the above-mentioned research reported the connection of HPV with specific vulvar cancer subtype VAIt.…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed previous reports of adenocarcinoma of intestinal-type of the vulva, and the report by Willén et al is likely a villous adenoma with an uncertain degree of dysplasia in the context of a colorectal adenoma [10]. Matsuzaki et al reported villoglandular adenocarcinoma of the vulva without stromal invasion [24], which could also be considered tubulovillous adenoma with high-grade dysplasia. The cases of adenocarcinoma of intestinal-type of the vulva are considered to have a good prognosis, but it may be possible to rede ne some of them as "adenoma.…”
Section: Discussionmentioning
confidence: 98%